Interplay between Shiraia and its fruiting body-associated Rhodococcus sp. No. 3 via hypocrellin A and carotenoid biosynthesis - Li Ping Zheng; Qun Yan Huang; Xin Ping Li; Jian Qin Zhou; Jian Wen Wang (Mycology, 2025)
Hypocrellin A (HA), a bioactive perylenequinone from Shiraia fruiting bodies, serves as an efficient photodynamic therapy photosensitiser. While these fruiting bodies harbour diverse bacteria, host-microbe functional interactions remain poorly characterised. This study elucidates a metabolite-mediated interplay between Shiraia sp. S9 and its fruiting body-associated bacterium Rhodococcus sp. No. 3. As non-contact co-cultivation significantly enhanced fungal HA production, bacterial volatile organic compounds (VOCs) such as dimethyl disulphide and 4-aminoacetophenone were identified for the elicitation. Bacterial VOCs increased fungal membrane permeability, induced reactive oxygen species (ROS) generation, and up-regulated HA biosynthetic gene expressions. Conversely, photoactivated HA induced cellular damage and growth inhibition on Rhodococcus sp. No. 3 via light-dependent ROS accumulation. Bacterial counteradaptation occurred through HA-induced carotenoid biosynthesis. This work provides the first evidence of a defense-driven feedback loop between Shiraia and its bacterial symbiont, revealing how VOCs act as biochemical elicitors while the photosensitiser HA shapes bacterial antioxidant responses. These insights advance our understanding of cross-kingdom interactions in fungal fruiting bodies and offer novel strategies for secondary metabolite enhancement.